Effect of operating conditions on catechin extraction from betel nuts using supercritical CO2-methanol extraction - Ruslan, M.S.H. (Taylor and Francis Inc., 2018)
In this work, the effect of extraction parameters on catechin extraction from betel nuts was studied. The supercritical carbon dioxide extraction parameters were pressure, temperature, and solvent flow rate while using average particle size of 177.5Â Î¼m and 5 (v/v) methanol as modifiers. Detection and quantification of catechin were achieved using HPLC analysis. The highest amount of extract and catechin concentration were 34.00Â mg extract/g sample and 565.38 ppm of catechin obtained at 30Â MPa, 70Â°C, and 4Â mL/min. The results given by optimization tools suggest the same operating conditions with less than 3 difference. Â© 2017 Taylor & Francis.